2000
DOI: 10.1161/01.str.31.7.1538
|View full text |Cite
|
Sign up to set email alerts
|

Differing Temporal Patterns of Onset in Subgroups of Patients With Intracerebral Hemorrhage

Abstract: Background and Purpose-The purpose of this study was to further analyze the temporal patterns of onset of intracerebral hemorrhage (ICH) and to determine whether or not subgroups with specific clinical characteristics exhibit different patterns of onset. Methods-The daily, weekly, and yearly variations in occurrence of ICH together with the relationship between ICH occurrence and changes in air temperature were evaluated in 1018 patients. Patients were grouped according to the presumed etiology of ICH: hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 80 publications
(120 reference statements)
6
47
0
2
Order By: Relevance
“…Several previous studies have shown that cerebral by guest on May 11, 2018 http://stroke.ahajournals.org/ Downloaded from hemorrhage occurs more frequently in the morning than during the remainder of the day. [18][19][20] Therefore, it may be important to reduce the frequency or duration of high blood pressure in the morning to prevent cerebral hemorrhage, and eating breakfast everyday might achieve this. Witbracht et al 21 suggested that skipping breakfast was associated with stress-independent overactivity in the hypothalamic-pituitary-adrenal axis because of a longer period of fasting, leading to elevated blood pressure in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that cerebral by guest on May 11, 2018 http://stroke.ahajournals.org/ Downloaded from hemorrhage occurs more frequently in the morning than during the remainder of the day. [18][19][20] Therefore, it may be important to reduce the frequency or duration of high blood pressure in the morning to prevent cerebral hemorrhage, and eating breakfast everyday might achieve this. Witbracht et al 21 suggested that skipping breakfast was associated with stress-independent overactivity in the hypothalamic-pituitary-adrenal axis because of a longer period of fasting, leading to elevated blood pressure in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have demonstrated that the incidence of stroke increases in the winter and spring and decreases in the summer and autumn. [3][4][5][6][7][8][9][10][11] However, some studies have reported increases in the incidence of stroke in response to dramatic temperature changes in the spring and autumn, [12][13][14] whereas in other studies, no seasonal variation has been demonstrated. [15][16][17] Because most previous studies have addressed large regions with varying climate, studies on smaller regions with similar weather and environments could provide important information on this topic.…”
mentioning
confidence: 99%
“…For SAH it has been suggested that hypertensive patients may be more susceptible to external stressors than normotensive patients [9, 11]. Previously analysis of our sample of ICH patients suggested that the occurrence of hypertensive ICH reflected seasonal and circadian variations in BP, whereas changes in BP did not seem to influence the occurrence of nonhypertensive ICH [5]. …”
Section: Discussionmentioning
confidence: 79%
“…BP has a seasonal pattern related to temperature with higher values in winter and lower values in summer [1], and a circadian rhythm related to the sleep-wake cycle with lower values during rest/sleep and inactivity, a rise on awakening and higher values during the rest of the day [2]. The winter and morning rises in BP have been invoked to explain the increased number of vascular events in the cold months [3, 4, 5, 6, 7]and in the morning waking hours [5, 8, 9, 10, 11, 12, 13, 14]. …”
Section: Introductionmentioning
confidence: 99%